The Role of Student Perception of Teacher Support on Student Engagement in Students - Fadhilah, Syifa; Akmal, Nur; Halima, Andi (Polteknik Ilmu Pemasyarakatan, 2025)
Student engagement in school is influenced by various factors, one of which is related to student perceptions of teacher support. Positive and negative student perceptions of the support provided affect student involvement in the classroom. This study aims to determine the role of student perceptions related to teacher support on student engagement. The method uses a quantitative approach method. The population in this study were 232 students of SMP X Makassar City with a sample of 145 students obtained through accidental sampling techniques. Data is collected through questionnaire use Scale student engagement adaptation of 22 items (CFI = 0.924; TLI = 0.903; RMSEA = 0.0497) with McDonald's reliability = 0.873 and the teacher support adaptation scale is 11 items (CFI = 0.955; TLI = 0.940; RMSEA = 0.0577) with McDonald's reliability = 0.853. The results of this study indicate that student perception of teacher support have role and manner significant influential towards student engagement among students at SMP X Makassar City with contribution amounting to 23.8%. Implications in study This is perception student related teacher support is influential on student engagement be a better teacher give capable support​ in effort For make student own positive perception​ related support provided by teachers.